Perspectives in the treatment of lung cancer: analysis of signaling pathways and biomarkers (Research, Society and Development, 2022)
Lung cancer has the highest incidence and the highest mortality rate in the world. Precision medicine has significantly improved therapeutic options, increasing survival rates. However, a significant number of patients are not eligible for targeted therapies. Thus, molecular characterization and definition of gene signatures based on pathway enrichment can be essential for clinical management and understanding of the therapeutic plan. The objective is to define molecular signatures, enriched pathways and biomarkers of non-small cell lung cancer (NSCLC), outlining a molecular panel of gene expression. The bibliographic study performed was a quick review, with searches in the Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SciELO) electronic databases, using the descriptors "lung cancer", “molecular signatures”, “enrichment of pathways” and “neoplastic biomarkers”. Therefore, it was possible to identify differentially expressed genes and their inscription in possible signaling pathways, which can be important therapeutic targets.